Keterampilan Menulis Tegak Bersambung Dan Media Alfabet â€œSenyawaâ€ - Trimayasari, Kundarti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
The purpose of this study was to determine the effect of the alphabet media " SENYAWA " to the improvement of writing skills continued straight grade II SD N Karangmulyo , Kab . Purworejo. This study approach used true experimental research. Pretest posttest control group used as research design. Treatment arrange on  8 meetings , each meeting consist of the alphabet using the media " SENYAWA ". The subjects of this study were 30 students who were divided into 2 groups: the experimental group and the control group. The data collection technique used writing skills observation. Data were analyzed using T test. The study  results showed that the media alphabet " SENYAWA" had  positive effect on students' writing skills upright continued . Based on the test results two groups conducted by the authors, obtained t < t table is -5.435 < 2.0484 and the average value of the experimental group in the amount of 8.46 with a percentage of 39.2 % . These results indicate that the writing skills upright concatenated experimental group is higher than the control group.